Intra-articular injections with corticosteroids and sodium hyaluronate for treating temporomandibular joint disorders: a systematic review - Machado,Eduardo (2013)
INTRODUCTION: In some cases, conservative treatment of internal derangements of the Temporomandibular Joint (TMJ) is considered little responsive. Thus, it is necessary to accomplish treatments that aim at reducing pain and improve patients' functions who present arthrogenic temporomandibular disorders. OBJECTIVE: This study, by means of a systematic review of the literature, aimed to analyze the effectiveness of intra-articular injections with corticosteroids and sodium hyaluronate for treating internal derangements of the TMJ. METHODS: Carry out a research in the following databases: MEDLINE, Cochrane, EMBASE, Pubmed, Lilacs, and BBO, considering publications issued between 1966 and October of 2010, focusing on randomized or quasi-randomized controlled clinical trials, single or double-blind. RESULTS: After applying the inclusion criteria we collected 9 articles, 7 of which were randomized controlled double-blind clinical trials and 2 randomized controlled single-blind clinical trials. CONCLUSION: After analyzing the literature, it was found that intra-articular injection with corticosteroids and sodium hyaluronate seems to be an effective method for treating internal derangements of the TMJ. However, further randomized controlled clinical trials, with representative samples and longer follow-up time must be carried out in order to assess the real effectiveness of this technique.